2021
DOI: 10.1177/2054358121993995
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Severity of Chronic Pain in Patients With Chronic Kidney Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Chronic pain is a common and distressing symptom reported by patients with chronic kidney disease (CKD). Clinical practice and research in this area do not appear to be advancing sufficiently to address the issue of chronic pain management in patients with CKD. Objectives: To determine the prevalence and severity of chronic pain in patients with CKD. Design: Systematic review and meta-analysis. Setting: Interventional and observational studies presenting data from 2000 or later. Exclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 92 publications
(341 reference statements)
1
15
1
3
Order By: Relevance
“…In our study, more than one-third of hemodialysis patients have chronic pain, similar to the prevalence in a Chinese study 20 . However, a systemic review and a previous study in Palestine reported a higher prevalence of chronic pain, 60.5% and 66.3%, respectively 9,25 . This difference could be due to different sample sizes or differences in pain perception among different cultures.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, more than one-third of hemodialysis patients have chronic pain, similar to the prevalence in a Chinese study 20 . However, a systemic review and a previous study in Palestine reported a higher prevalence of chronic pain, 60.5% and 66.3%, respectively 9,25 . This difference could be due to different sample sizes or differences in pain perception among different cultures.…”
Section: Discussionmentioning
confidence: 78%
“…A systematic review of 52 studies involving 6,917 HD patients from 10 countries 171 reported that the prevalence of chronic pain ranged from 33 to 82%, whereas the prevalence of acute pain (defined as current pain, intradialytic pain or pain during the past 4 weeks) ranged from 21 to 92%. A subsequent systematic review and meta-analysis of 48 studies involving 8,464 patients on dialysis from 23 countries 172 , showed that the mean prevalence of chronic pain was 60.5%. However, the researchers noted that studies lacked a uniform approach to defining the chronicity and nature of pain, and that the tools used to determine pain severity were variable.…”
Section: Global Patient-reported Outcomesmentioning
confidence: 99%
“…In the economic category, while people who had not received In the physical category, participants without kidney transplantation are identified as a condition for quality of life, a common and often severe manifestation in various populations with CKD; with prevalence's of 40% to 60% is a strong imperative to establish the management of chronic pain as a clinical and research priority [33]. In this regard, the labels acute and chronic pain are available in NANDA-I [20].…”
Section: Discussionmentioning
confidence: 99%